739 Development of patient-derived models of esophageal cancer for GUCY2C-directed immunotherapeutic testing. (9th November 2020) - Weindorfer, Megan; Lisby, Amanda; Zalewski, Alicja; Baybutt, Trevor; Carlson, Robert; Crutcher, Madison; Loren, David; Rosato, Ernest; Evans, Nathaniel; Waldman, Scott; Snook, Adam
Abstract : Background: Esophageal cancer is the fifth most common cause of cancer-related death in the world 1 with a 5-year survival rate of <20%. 2 Current therapies result in high toxicity and low efficacy, with as many as 60% of esophageal cancer patients not responding to therapeutics. 3 CAR-T cell therapy is a therapeutic that can selectively and robustly target cancer cells and eliminate bulky metastatic disease. Previous studies have shown preclinical success with CAR-T cell therapy targeting the human colorectal cancer antigen guanylyl cyclase C (GUCY2C). 4 5 Interestingly, esophageal cancers arising from premalignant metaplasia resembling intestine (intestinal metaplasia, also known as Barrett's esophagus) are highly prevalent and ectopically express GUCY2C. Thus, we hypothesize that GUCY2C will serve as an effective CAR-T cell therapy target in many esophageal cancer patients. However, the paucity of intestine-like human esophageal cancer models limits exploration of this hypothesis, necessitating development of suitable esophageal cancer models (figure 1). Methods: To develop esophageal cancer models for GUCY2C immunotherapy testing, esophageal cancer samples were collected at Thomas Jefferson University Hospital by endoscopic biopsy of treatment-naïve patients or by esophagectomy, primarily in patients previously treated with standard neoadjuvant therapy. Patient-derived xenograft (PDX) models were initiated from samples to establish in vivo models for immunotherapy testing. qRT-PCR, immunoblot, and immunofluorescence were performed to test for GUCY2C expression in primary and PDX specimens. Histopathology was performed to confirm retention of primary tumor features. Results: GUCY2C was present in only 2 of 6 esophagectomy samples. Interestingly, those patients with detectable GUCY2C were treatment-naïve, while neoadjuvant-treated patients lacked viable tumor, revealing neoadjuvant therapy as a significant barrier to esophageal cancer model generation. In contrast, of the 3 adenocarcinoma specimens collected by endoscopic biopsy in treatment-naïve patients, 2 express GUCY2C. To date, PDX models have been initiated from 6 total samples and successfully established for 3 samples. This 50% success rate may improve over time as PDX formation is often delayed in many models (>150 days). Importantly, established esophageal adenocarcinoma PDX models were histologically similar to their matched primary tumors and retained GUCY2C expression, integral to their validation as models of GUCY2C immunotherapy testing. Conclusions: Several human esophageal adenocarcinoma models were successfully established, primarily from endoscopic biopsy of treatment-naïve patients as neoadjuvant therapy proved to be a significant barrier. These models will be useful to explore GUCY2C-directed CAR-T cell therapies and other novel therapies targeting intestine-like esophageal cancer, prior to testing in early-phase clinical trials. Acknowledgements: The authors thank the Translational Research & Pathology Core Facility and the Office of Animal Resources at Thomas Jefferson University for their continued support to make this research possible. The authors would also like to thank the Clinical Research Unit at Thomas Jefferson University for their assistance in the collection of patient specimens. This work was supported by a DeGregorio Family Foundation Award and by the Department of Defense Congressionally Directed Medical Research Programs (W81XWH-17-1-0299, W81XWH-191-0263, and W81XWH-19-1-0067) to AES. SAW is supported by the National Institutes of Health (NIH) (R01 CA204881, R01 CA206026, and P30 CA56036), the Defense Congressionally Directed Medical Research Program W81XWH-17-PRCRP-TTSA, and Targeted Diagnostic & Therapeutics. SAW and AES were also supported by a grant from The Courtney Ann Diacont Memorial Foundation. SAW is the Samuel M.V. Hamilton Professor of Thomas Jefferson University. AZ and MC were supported by NIH institutional award T32 GM008562 for Postdoctoral Training in Clinical Pharmacology. Ethics Approval: The study was approved by the Thomas Jefferson University Institutional Review Board (#18D.495) and Institutional Animal Care and use Committee (#01529). References: Bray F, Ferlay J, Soerjomataram I, Siegel RL, Torre LA, Jemal A. Global cancer statistics 2018: GLOBOCAN estimates of incidence and mortality worldwide for 36 cancers in 185 countries. CA Cancer J Clin 2018;68:394–424. doi:10.3322/caac.21492. Yousefi MS, Sharifi-Esfahani M, Pourgholam-Amiji N, Afshar M, Sadeghi-Gandomani H, Otroshi O, et al. Esophageal cancer in the world: incidence, mortality and risk factors. Biomed Res Ther 2018;5:2504–17. doi:10.15419/bmrat.v5i7.460. Huang F-L, Yu S-J. Esophageal cancer: risk factors, genetic association, and treatment. Asian J Surg 2018;41:210–5. doi:10.1016/j.asjsur.2016.10.005. Magee MS, Abraham TS, Baybutt TR, Flickinger JC, Ridge NA, Marszalowicz GP, et al. Human GUCY2C-targeted chimeric antigen receptor (CAR)-expressing T cells eliminate colorectal cancer metastases. Cancer Immunol Res 2018;6:509–16. doi:10.1158/2326-6066.CIR-16-0362. Magee MS, Kraft CL, Abraham TS, Baybutt TR, Marszalowicz GP, Li P, et al. GUCY2C-directed CAR-T cells oppose colorectal cancer metastases without autoimmunity. Oncoimmunology 2016;5:e1227897. doi:10.1080/2162402X.2016.1227897.